2018
DOI: 10.4236/ajcc.2018.74038
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Farmers’ Perception and Adaptation Strategies to Climate Change and Variability in Bako Tibe, Ethiopia and Abeokuta, Nigeria

Abstract: Comparing the perception of farmers to climate change and variability in Bako Tibe, Ethiopia and Abeokuta, Nigeria is important in promoting sustainable agriculture and in understanding the impact of climate change and variability on agriculture in Africa. A total of 153 farmers were interviewed in both study areas using well structure questionnaire. The study describes the socioeconomic characteristics of farmers using descriptive statistics and thereafter the perception of Bako Tibe and Abeokuta farmers to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Early and late planting (changing sowing period) adaptation strategy was practiced in North West Ethiopia as indicated by Mequannt et al (2020) and Oranu et al, (2018). In the current study the changes in the season corresponded to changes in the climatic conditions.…”
Section: Climate Change Resilience Strategies Adopted In Muyembe Sub-...supporting
confidence: 53%
See 2 more Smart Citations
“…Early and late planting (changing sowing period) adaptation strategy was practiced in North West Ethiopia as indicated by Mequannt et al (2020) and Oranu et al, (2018). In the current study the changes in the season corresponded to changes in the climatic conditions.…”
Section: Climate Change Resilience Strategies Adopted In Muyembe Sub-...supporting
confidence: 53%
“…These were chosen as wonder crops for they are fast maturing and have a high potential of yielding at least double the indigenous crops. Mburu et al (2015) and Oranu et al, (2018) also indicated that growing drought-tolerant crop varieties was one of the most common and vital adaptation strategies in practice on small-scale farms in Kenya. The difference in crops is attributable to heterogeneity of geographical regions and agro-ecological settings.…”
Section: Climate Change Resilience Strategies Adopted In Muyembe Sub-...mentioning
confidence: 99%
See 1 more Smart Citation
“…Using an interval scale of 0.05, the upper limit is 3.05 while the lower limit is 2.95. Scores equal to or above 3.0 were considered as serious constraint while those equal to or below 2.95 were regarded as not serious constraints following ORANU et al (2018). The level of participation of women in agricultural activities was ascertained using participation index.…”
Section: Analytical Techniquesmentioning
confidence: 99%
“…Five chicken breeds (S-RIR, Sasso, Horro, Kuroiler and Koekoek) were distributed over 222 households, 13 villages, 5 districts (Adami Tulu, Bako Tibe, Dano, Dugda and Haromaya), 3 zones (East Hararge, East and West Shoa), one cool sub humid agro-ecological zone in Oromia, Ethiopia. (Shiferaw, 2008, de Putter et al, 2012 (Oromia BOFED, 2009) (Oranu et al, 2018) ( Kassie et al, 2007) For reliability, data cleaning was conducted. Data of households containing eggs of hens before ACGG breed introduction was deleted to prevent miscounting.…”
Section: Data Collection and Cleaningmentioning
confidence: 99%